1999
DOI: 10.1021/jp991997z
|View full text |Cite
|
Sign up to set email alerts
|

Method for Including the Dynamic Fluctuations of a Protein in Computer-Aided Drug Design

Abstract: We have recently presented a new pharmacophore design method that allows for the incorporation of the inherent flexibility of a target active site. The flexibility of the enzymatic system is described by collecting many conformations of the uncomplexed protein; this ensemble of conformational states can come from a molecular dynamics (MD) simulation, multiple crystal structures, or many NMR structures. Binding sites for functional groups that complement the active site are determined through multiple-copy calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 33 publications
0
99
0
3
Order By: Relevance
“…Even the use of just two crystal-structure models produced improved results over single-structure models. 103 McCammon and co-workers 104 introduced the so-called relaxed-complex scheme, which takes into account the possibility that a ligand may bind to only a few conformations of the receptor. A long MD simulation of the apo receptor is first conducted to sample extensively its conformational space, followed by the rapid docking of mini-libraries of candidate inhibitors against a large ensemble of snapshots.…”
Section: Docking Into Several Individual Protein Conformationsmentioning
confidence: 99%
“…Even the use of just two crystal-structure models produced improved results over single-structure models. 103 McCammon and co-workers 104 introduced the so-called relaxed-complex scheme, which takes into account the possibility that a ligand may bind to only a few conformations of the receptor. A long MD simulation of the apo receptor is first conducted to sample extensively its conformational space, followed by the rapid docking of mini-libraries of candidate inhibitors against a large ensemble of snapshots.…”
Section: Docking Into Several Individual Protein Conformationsmentioning
confidence: 99%
“…An increasing amount of experimental evidence, such as the recognition of dissimilar ligands (47) and the enhancement of antibody affinity and specificity by making the unbound state more similar to the bound state (5), supports such a model. The use of ''dynamic'' pharmacophore models in such calculations has already led to improved results (48); these models have been derived from either MD (48) or several crystal structures chosen in a similar way to the HSP ensembles (49). Hence, HSP ensembles or ensemble-refined experimental structures (30) represent a possible alternative to MD simulations for the purpose of ensemble generation.…”
Section: Nmr Order Parametersmentioning
confidence: 99%
“…The coupling may be introduced, in fortunate cases, as a local coupling between the connecting atomic orbitals of donor and bridge and bridge and acceptor, multiplied by a transfer capability function that is a property of the bridge. 7 Nelsen's group has shown that the rate constants for intramolecular electron transfer within several aromatic-bridged bis(hydrazine) radical cations are accurately predicted using the simple Marcus twostate model with electron transfer parameters derived from their optical spectra. 8 However, for one case (that having 9,10-anthracenediyl as the bridge), intramolecular electron transfer was much faster than predicted from the two-state model, and the optical spectrum was anomalous.…”
mentioning
confidence: 99%